Perspectives on the Development of Filter Media for Point of Use Water Filters: Case Study of Arsenate Removal - Chigome, Samuel; Andala, Dickson; Kabomo, Moses; Mobegi, Erick (Frontiers in Chemistry, 2022)
The demand for access to clean drinking water will continue to increase as the world population increases. The current population of Africa is 1.38 billion and the number of people who do not have access to clean drinking water in Africa is 400 million which is projected to get to 600 million by 2025, with the majority being those living in rural settings. The majority of the people who do not have access to clean drinking water are those in settings that are far away from centralized municipal water treatment systems which has resulted in an increased need for gravity or solar driven point of use water filters. Furthermore, the change in perception of health standards has resulted in an increased need for further purification of municipal water either as water bottles, tap outlet filters or kitchen countertop filters. For sustainable development and embracement of technological advancement, it is plausible to consider a filter material development approach that uses abundant locally available natural resources as the raw material and nanotechnology techniques for material fabrication. The article will present perspectives of the authors as guided mostly by the work performed in their laboratories on how to embrace nanotechnology and abundant locally available materials for filter media development. This will include a case study on a new chitosan, aluminium, titanium, iron, and zirconium (CTS-Al-Ti-Fe-Zr) nanocomposite that was fabricated through the sol-gel process for the removal of arsenate from water. The experimental data fitted well with the Langmuir isotherm model with a maximum adsorption capacity of 123 mg/g. The results from the study revealed that CTS-Al-Ti-Fe-Zr nanocomposite is a promising filter media since it could reduce the concentration of As(V) in drinking water to less than 10 ppb thus meeting the guideline limit of arsenic in drinking water as regulated by the WHO. The fabricated gravity-based prototype filter laden with 60 g of the CTS-Al-Ti-Fe-Zr nanocomposite was able to purify 650 L of tap water.